Eutrema EsMYB90 Gene Improves Growth and Antioxidant Capacity of Transgenic Wheat Under Salinity Stress - Li, Chuanshun; Zhao, Yaoyao; Qi, Yuting; Duan, Chonghao; Zhang, Hengyang; Zhang, Quan (Frontiers in Plant Science, 2022)
The ectopic expression of the EsMYB90 transcription factor gene from halophytic Eutrema salsugineum has been reported to enhance the level of anthocyanin and other flavonoid metabolites in transgenic tobacco. In this study, the wheat JW1 overexpressing EsMYB90 showed longer roots and higher fresh weight than that in wild type (WT) under salt stress. In addition, the transgenic wheat plants displayed significantly higher peroxidase (POD) and glutathione S-transferase (GST) activity, as well as markedly lower malondialdehyde (MDA) content than that of the WT during salt stress conditions. The analysis of histochemical staining and H2O2 level indicated that the accumulation of reactive oxygen species (ROS) was significantly lower in the roots of transgenic wheat plants compared to the WT under salt stress. Transcriptome analysis revealed that the EsMYB90 gene affected the expression of considerable amounts of stress-related genes that were involved in phenylpropanoid biosynthesis and antioxidant activity in transgenic plants subjected to NaCl treatment. Importantly, the significantly upregulated expression genes in transgenic wheat under salt stress were mainly associated with the antioxidative enzymes POD and GST encoding genes compared with the WT. Furthermore, EsMYB90 is suggested to bind with the MYB-binding elements of pTaANS2 and pTaDFR1 by dual luciferase assay, to activate the transcription of TaANS2 and TaDFR1 genes that are encoding key enzymes of anthocyanin biosynthesis in transgenic wheat plants. All the results indicated that, under salt stress, the EsMYB90 gene plays a crucial role in preventing wheat seedlings from oxidative stress damage via enhancing the accumulation of non-enzymatic flavonoids and activities of antioxidative enzymes, which suggested that EsMYB90 is an ideal candidate gene for the genetic engineering of crops.